Demographic and Clinical Profile of Non-Addicted Schizophrenia Patients (NASH) in Lahore, Pakistan - Ishrat Aziz; Saadat Ali; Atika Hashmi; Azka Asghar; Sajjad Ali Sajjad; Sadaf Abdul Qadir (Journal of Health, Wellness and Community Research, 2025)
Background: Schizophrenia is a debilitating psychiatric disorder with diverse etiological models and clinical subtypes. While cannabis use is a recognized environmental trigger, limited research exists on schizophrenia in non-addicted individuals, particularly within culturally diverse, resource-constrained settings. Understanding demographic distributions, subtype prevalence, and patient-perceived causes in such populations is crucial for culturally informed care. Objective: To determine the socio-demographic profile, DSM-IV-based clinical subtypes, and explanatory beliefs regarding schizophrenia among non-cannabis addicted patients in Lahore, Pakistan. Methods: A cross-sectional study was conducted from January to December 2021 at the Punjab Institute of Mental Health and Blessings Rehabilitation Centre in Lahore. A total of 81 patients diagnosed with schizophrenia per DSM-IV criteria and with no history of cannabis use were enrolled. Data were collected through a structured three-part questionnaire assessing demographic characteristics, subtype classification, and causal attributions using a culturally adapted clinical vignette. Descriptive and inferential statistics were analyzed using SPSS. Results: The majority of patients were aged 31–44 years (43.2%) with a slight female predominance (51.9%). Catatonic subtype was most frequent (34.6%). Mental illness (81.5%) and religious beliefs (35.8%) were the most commonly perceived causes. Family history was reported in 24.7% of cases, with no significant association across subtypes. Conclusion: Non-addicted schizophrenia patients in this setting exhibited distinct demographic patterns and culturally shaped causal beliefs, highlighting the need for personalized, culturally sensitive psychiatric interventions that address both biomedical and sociocultural frameworks.
Keywords: Schizophrenia, Non-Cannabis, Subtypes, Cultural Beliefs, DSM-IV, Mental Health, Pakistan.